Natural Resource and Watershed Management in South Asia: A Comparative Evaluation with Special References to Nepal - Tiwari, Krishna R.; Bajracharya, Roshan M.; Sitaula, Bishal K. (Journal of Agriculture and Environment, 2009)
The paper discusses different approaches of watershed management programs implemented in South Asian countries, with special reference to Nepal based on existing literature and field experiences. Watershed degradation, particularly in mountainous areas, is critical problem in South Asian countries. A participatory approach has been adopted in watershed and natural resource management during the last decade in many developing countries. The participatory community-based watershed management approach in Nepal is viewed from two perspectives. The first, success of conservation of natural resources with formation and strengthening of the local level institutions in rural areas of the country; the second, its multiplier effects in social mobilization, women empowerment, community development and livelihood improvement as well as good governance at local level. In the present context, participatory watershed management must include not only environmental protection but also supporting poor and disadvantaged segments of society in improving their livelihoods. Key words: Bottom-up approach; Empowerment; Participatory approach; Resource management; Top-down approach and watershed degradation The Journal of Agriculture and Environment Vol:.9, Jun.2008 Page: 72-89